2000
DOI: 10.1002/(sici)1097-0029(20000301)48:5<241::aid-jemt2>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the gastric mucosa

Abstract: A plethora of neuronal messengers (“classical” transmitters, gaseous messengers, amino acid transmitters, and neuropeptides) are capable of mediating or modulating gastric functions. Accordingly, the stomach is richly innervated. Gastric nerves are either intrinsic to the gastric wall, i.e., they have their cell bodies in the intramural ganglia and thus belong to the enteric nervous system, or they reach the stomach from outside, originating in the brainstem, in sympathetic ganglia, or in sensory ganglia. Topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 121 publications
1
21
0
1
Order By: Relevance
“…Over the last years, the morphology of the gastric myenteric plexus and the neurochemical coding of its neurons have been extensively studied using many different techniques (for a review see Ekblad et al, 2000). Both radioimmunoassay (Ferrante et al, 1991;Hannibal et al, 1998;El-Salhy, 1999), and immunocytochemistry (recently Jarvinen et al, 1999;Reiche and Schemann, 1999;Vanden Berghe et al, 1999;Hu et al, 2002;Pfannkuche et al, 2003;Pimont et al, 2003) have revealed that neuronal elements of the stomach express a wide spectrum of various neurotransmitters including neuropeptides.…”
supporting
confidence: 63%
“…Over the last years, the morphology of the gastric myenteric plexus and the neurochemical coding of its neurons have been extensively studied using many different techniques (for a review see Ekblad et al, 2000). Both radioimmunoassay (Ferrante et al, 1991;Hannibal et al, 1998;El-Salhy, 1999), and immunocytochemistry (recently Jarvinen et al, 1999;Reiche and Schemann, 1999;Vanden Berghe et al, 1999;Hu et al, 2002;Pfannkuche et al, 2003;Pimont et al, 2003) have revealed that neuronal elements of the stomach express a wide spectrum of various neurotransmitters including neuropeptides.…”
supporting
confidence: 63%
“…It is also of note that CGRP and neurokinin A synergistically increased mucus secretion. The gastric mucosal protection exerted by CGRP, which has been well described, is considered to be attributable to the suppressed acid output and/or increased mucosal blood flow caused by CGRP (32,33,36,37). Taken together with the most recent study indicating modulation by CGRP of mucin synthesis in rat gastric mucosa (38), our results would add stimulation of mucus secretion to the list of the potential mechanisms underlying the gastric mucosal protection due to CGRP.…”
Section: Discussionmentioning
confidence: 99%
“…play an important role in mucosal protection (32,33) and may be stimulated by the PAR-2 agonist as described above. CGRP, administered intravenously in a dose range of 0.028-2.8 nmol/kg, in combination with amastatin, remarkably triggered secretion of gastric mucus in a dosedependent manner (Figure 3a, left panel).…”
Section: Figurementioning
confidence: 99%
“…TRPM8 and TRPA1 are activated by cold temperatures (1)(2)(3)(4). In addition to certain sensory neurons, selected TRPV members have been reported to be expressed on mast cells (5) and in the gastric mucosa (6).…”
mentioning
confidence: 99%